Calcium ion significance on the maintenance of barley (Hordeum vulgare) chromosome compaction. (June 2021) - Siregar, Aldi Yazri; Sartsanga, Channarong; Arifudin, Fendi Sofyan; Phengchat, Rinyaporn; Salamah, Andi; Ohmido, Nobuko; Fukui, Kiichi; Dwiranti, Astari
Highlights: The first report on the effects of calcium ions on plant chromosome structure. Calcium ions are essential for the maintenance of barley chromosome structure. Chromosomes showed less condensed structure due to calcium ions chelation. Scanning electron microscopy is advantageous for chromosome ultrastructure study. The ionic liquid is useful for chromosome observation by scanning electron microscope. Abstract: Cations, especially calcium ions (Ca 2+ ), is one of the major factors responsible for the chromosome higher-order structure formation. The effects of cations on the human chromosomes have already been evaluated, however, whether the presence of similar effects on plant chromosomes has not been reported to date. Thus, in this study, we investigated the role of Ca 2+ on the barley ( Hordeum vulgare L.) chromosome structure. Barley chromosomes were isolated from the meristematic tissue within the germinated roots. The roots were subjected to enzymatic treatment, fixed, and drop on the cover glass to spread the chromosomes out. Some chromosomes were treated with BAPTA (1, 2-Bis(2-aminophenoxy)ethane-N, N, N', N'-tetraacetic acid) to chelate Ca 2+ . Chromosome samples were then observed by fluorescence microscopy and scanning electron microscopy (SEM). The disperse structure of the chromosome was observed after BAPTA treatment. Chromosomes showed less condensed structure due to Ca 2+ chelation. The high-resolution of SEM provided a more detailed visualization of chromosome ultrastructure under different calcium ion conditions. This study revealed the calcium ion effect on chromosome structure is important regardless of the organisms, suggesting a similar mechanism of chromosome condensation through humans and plants.